Unstable anginal syndrome and pulmonary oedema due to thyrotoxicosis. Issue 783 (January 1991) - Glikson, M.; Freimark, D.; Leor, R.; Shechter, M.; Kaplinsky, E.; Rabinowitz, B.
Abstract : We report on a 40 year old woman who presented with typical unstable angina pectoris associated with pulmonary oedema, due to poorly controlled hyperthyroidism. No cardiac abnormality was detected by echo-Doppler and nuclear ventriculography. Coronary angiography demonstrated normal coronary arteries. This case represents a new manifestation of the known association of cardiac ischaemia with hyperthyroidism in the presence of normal coronary arteries.